Effect of Quenching Medium and Tempering Temperature on Microstructure and Hardness of JIS SUP 9 Steel: Pengaruh Media Pendingin dan Temperatur Tempering pada Mikrostruktur dan Kekerasan Baja JIS SUP 9 - Andrie Harmaji; Akhmad Ardian Korda; Rama Ramadhan; Satrio Pambudi (Journal of Renewable Energy and Mechanics, 2023)
JIS SUP 9 steel is one of the materials commonly used for suspension components in motorized vehicles with medium carbon steel base material. It must have good hardness and toughness so that failure does not occur during operational. This research was conducted to increase the hardness of JIS SUP 9 Steel through a heat treatment and various quenching media. The heat treatment was carried out with 830-880ºC temperature with a holding time of 7 minutes then cooled using water and oil. After treatment, tempering was carried out with a holding time of 7 minutes and then cooled in room temperature. Hardness testing was carried out using Microhardness Vickers and then the microstructure was observed using an Olympus Metallurgical Microscope. The results show that heat treatment followed by rapid cooling increases the initial hardness of JIS SUP 9 (229 VHN) steel. The decrease in hardness after the tempering process will be higher with increasing tempering temperature. The results of the microstructure of the sample without heat treatment showed pearlite and ferrite phases. After heat treatment, tempered martensite, residual austenite and carbide phases appear. It can be concluded that changes in the microstructure affect the hardness of JIS SUP 9 steel.